(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The impact of temperature and photoperiod on the development science, life span, fertility and nourishment consumption of N. rufipes. Studies were additionally completed on the impact of biopesticides on the egg, larval stages and grown-ups of the vermin. A thorough study of the fish drying techniques, the nuisances pervading the dried fish and strategies for control drilled by the fishermen are additionally included. Studies on N.rufipes as a bug of dried fish are immaterial in India and this work may fill in the lacunae somewhat .Dried fish forms a major source of protein in a number of equatorial countries. Dried fishery products frequently suffer severe losses due to infestation by flesh flies (Sarcophagidae), beetles (Dermestes, Cornestes, and Necrobia spp.), and mites (Lardoglyphus and Lyrophagus spp.).Dried fish contaminated by both insects and harmful insecticides comprises about 80 percent of the total dried products that is considered unfit for human consumption. The losses have been attributed to net reductions in the amount of nutrients available to the consumer (nutritive quality) resulting to declining consumer acceptability and market prices (economic losses) or both quantitative and qualitative losses.